Accelerated partial breast irradiation: Macrophage polarisation shift classification identifies high-risk tumours in early hormone receptor-positive breast cancer - Schnellhardt, Sören; Erber, Ramona; Büttner-Herold, Maike; Rosahl, Marie Charlotte; Ott, Oliver; Strnad, Vratislav; Beckmann, Matthias; King, Lillian; Hartmann, Arndt; Fietkau, Rainer; Distel, Luitpold (Cancers, 2020)
Studies have demonstrated correlations between accumulations of tumour-associated macrophages (TAMs), especially of M2-like phenotype, and increased mortality in advanced breast cancer. We investigated the prognostic potential of both main macrophage phenotypes in early hormone receptor-positive (HR+) breast cancer. The studied cohort of 136 patients participated in an institutional APBI phase II trial. Patient selection was characterized by HR+, small tumour size and no metastasis. Tissue microarrays from pre-RT resection samples were double stained for CD68/CD163 using immunohistochemistry. CD68+/CD163− cells were considered M1-like macrophages and CD68+/CD163+ was representative of M2-like macrophages. M1 and M2 macrophage densities were analysed semi-automatically in the stromal and intraepithelial tumour compartment. Low M1 and high M2 densities were strongly associated with decreased disease-free survival (DFS). Combined TAM phenotype densities were studied after defining a macrophage shift classification: M1-shifted (M1 high, M2 low) and non-shifted (M1 low, M2 low; M1 high, M2 high) tumours entailed a favourable outcome. In contrast, M2-shifted (M1 low, M2 high) TAM populations were associated with extremely reduced DFS. Thus, the full predictive potential of TAMs was revealed in a combined analysis of both phenotypes. The M2-shifted subgroup of tumours is classified as high-risk and probably not suitable for partial breast irradiation.
CRIS-Team Scopus Importer:2020-02-25
Keywords: Accelerated partial breast irradiation; CD163; CD68; Early breast cancer; Hormone receptor-positive; Prognosis; Tumour associated macrophages